Multisystem Langerhans' cell histiocytosis with pancreatic involvement. Issue 4 (April 1993) - Yu, R C; Attra, A; Quinn, C M; Krausz, T; Chu, A C
Abstract : Langerhans' cell histiocytosis, a rare disorder of unknown cause affecting both children and adults, can affect many different organs and present to a wide range of medical specialties. An infant with fatal multisystem Langerhans' cell histiocytosis in whom the pancreas and the intestine were extensively affected is reported. The direct pancreatic involvement by this disease has not previously been described.